Perbandingan Konsep Penawaran Dalam Ekonomi Konvensional Dan Islam: Studi Literatur Kualitatif - Rafida Z; Mohd Winario (EL-EMIR Institute, 2026)
This study examines the comparative concept of supply from the perspective of conventional economics and Islamic economics through a qualitative literature study approach. The concept of supply is a fundamental element in market mechanisms that determine the equilibrium price and quantity of goods and services. In conventional economics, supply is driven by the motive of maximizing profit and production efficiency without explicit consideration of moral, ethical, and social responsibility aspects. The orientation of economic rationality tends to focus solely on individual interests and the achievement of material gain. Meanwhile, Islamic economics integrates sharia values into every aspect of supply, including the prohibition of usury, gharar, and maysir, as well as the obligation to maintain justice, transparency, and the welfare of the community. Through a comparative analysis of various relevant literature, this study finds that fundamental differences lie in the objectives, basic principles, and mechanisms used in supply. Islamic economics emphasizes the balance between this world and the hereafter, social justice, proportional distribution, and responsibility to Allah SWT. The practical implication is the need for a more holistic reorientation of the economic system by integrating economic efficiency with moral-spiritual values.